ESTIMATES OF FRACTURE AND PERMEABILITY OF ROCKS IN WELL SECTIONS ACCORDING TO THE PREDICTING METHOD - SKAKALSKA, Ludmyla; NAZAREVICH, Andriy; KOSARCHYN, Volodymyr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to highlighting the methods of studying the petrophysical characteristics of rocks using the developed theoretical-empirical method for predicting the oil and gas capacity of well sections and their results. As a part of the predictive method, methods for determining a number of important petrophysical characteristics of rocks in well sections were additionally developed. In particular, cracking and permeability of rocks is estimated by the indicator of crack opening – the Qside parameter, the strength of rocks is estimated by volume density and velocities of elastic bulk waves, and the types of rocks in layers are determined by a set of petrophysical parameters, including the density of the solid phase of rocks. The determining results of these parameters in sections for wells 4-North-Zarichnyans'ka and 1-Lishchyns'ka, are given.
Keywords: well section; predicting of oil and gas capacity; the theoretical-empirical technique; a layer rock type; elastic bulk wave velocities; rock strength; fracturing; permeability